2021
DOI: 10.1097/jat.0000000000000165
|View full text |Cite
|
Sign up to set email alerts
|

Current Clinical Practices of Saudi Physiotherapists in Stroke Rehabilitation

Abstract: Background and Purpose: Stroke is a major cause of disability and the third leading cause of death worldwide. Clinical practice guidelines for stroke rehabilitation identify stroke physiotherapists as an essential interdisciplinary team member to minimize residual impairments and disability, thereby improving the patient's ability to execute daily tasks. This article uses an existing American survey to compare Saudi physiotherapists' current practice and preferred interventions in stroke rehabilita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Research has shown that when deciding which modalities or treatment programs to incorporate into their practice, physiotherapists rely on their initial training, the treatment techniques they learned during their initial training, their personal experience, prior trials with the effects of a treatment, continuing education concerned with practice that guides practice discussions and expert opinions, and the advice of colleagues (Alatawi, 2021). A recent survey of Saudi physiotherapists' preferred approaches to stroke rehabilitation revealed a need for increased education, experience, and understanding among the practitioners (Alanazi & Alrwaily, 2022).…”
Section: Physical Therapy Research and Practicementioning
confidence: 99%
“…Research has shown that when deciding which modalities or treatment programs to incorporate into their practice, physiotherapists rely on their initial training, the treatment techniques they learned during their initial training, their personal experience, prior trials with the effects of a treatment, continuing education concerned with practice that guides practice discussions and expert opinions, and the advice of colleagues (Alatawi, 2021). A recent survey of Saudi physiotherapists' preferred approaches to stroke rehabilitation revealed a need for increased education, experience, and understanding among the practitioners (Alanazi & Alrwaily, 2022).…”
Section: Physical Therapy Research and Practicementioning
confidence: 99%
“…The handling of people with stroke is an essential part of PTs' practice (5,6). The results of systematic reviews show that many PTs with WRMDs suffered these injuries while lifting and transferring patients (7).…”
Section: Jrm-ccmentioning
confidence: 99%
“…All participants in stroke rehabilitation considered patient handling crucial (5,6,8,9). Further investigation is needed to investigate the efficacy of the approach used for stroke rehabilitation.…”
Section: The Handling Of People In Stroke Rehabilitation and Its Impl...mentioning
confidence: 99%
“…Therapeutic exercise with a focus on task specific training is the most utilized physiotherapy modality for stroke survivors. [8] It can be delivered either through individual or group session; with the group session normally conducted in a form of circuit class exercise. During circuit exercise session, a group of three or more participants is supervised by 2 to 3 physiotherapists in performing repetitive practice of a number of tasks which arranged in several workstations in sight of each other.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic exercise with a focus on task specific training is the most utilized physiotherapy modality for stroke survivors [8] . It can be delivered either through individual or group session; with the group session normally conducted in a form of circuit class exercise.…”
Section: Introductionmentioning
confidence: 99%